2008
DOI: 10.1002/jgm.1185
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant gene delivery of feline granulocyte‐macrophage colony‐stimulating factor using magnetofection for the treatment of feline fibrosarcomas: a phase I trial

Abstract: Despite aggressive pre- or postoperative treatment, feline fibrosarcomas have high recurrence rates. Immunostimulatory gene therapy is a promising approach in veterinary oncology. This phase I dose-escalation study was performed to determine toxicity and feasibility of gene therapy with feline granulocyte-macrophage colony-stimulating factor (feGM-CSF) in cats with fibrosarcomas. Twenty cats were treated with plasmid coding for feGM-CSF attached to magnetic nanoparticles in doses of 50, 250, 750 and 1250 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…Only three other research groups had used magnetofection for the treatment of tumors in vivo, and demonstrated its efficiency, safety and potential use for the delivery of therapeutic genes. 11,46,47,48,49 However, only in two studies was antitumor effect of magnetofection with therapeutic genes demonstrated. In the first study magnetofection was investigated in combination with RNAi, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Only three other research groups had used magnetofection for the treatment of tumors in vivo, and demonstrated its efficiency, safety and potential use for the delivery of therapeutic genes. 11,46,47,48,49 However, only in two studies was antitumor effect of magnetofection with therapeutic genes demonstrated. In the first study magnetofection was investigated in combination with RNAi, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was well-tolerated by most of the animals [49]. In a follow up phase I trial, preoperative felGM-CSF gene therapy had favorable results as assessed by the rate of recurrence in treated versus (surgery-only) control cats [50]. More recently, Tresilwised et al [7] examined the potential of boosting the efficacy of the oncolytic adenovirus dl520 by associating it with MNP and performing magnetic field-guided infection in multidrug-resistant cancer cell cultures and in a murine xenograft model.…”
Section: Therapeutic Potential Of Magnetic Gene Targeting In Vivo Cancermentioning
confidence: 92%
“…In addition, magnetofection contributed to site-specific delivery of antisense oligonucleotides as well as reporter genes attached to SPIONs in vivo (Krötz et al 2003a; Scherer et al 2002). Recently, two trials consisting of dose-escalation neoadjuvant gene therapy to surgery were performed in feline fibrosarcomas in which therapeutic genes were applied by magnetofection (Hüttinger et al 2008; Jahnke et al 2007). The use of SPIONs either as a drug or gene delivery system contributes to the effectiveness of the therapy in many ways.…”
Section: Introductionmentioning
confidence: 99%